(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article discusses the application of geoinformation systems and mathematical statistics methods for spatial data analysis in ecology and geography. The necessity of integrating GIS technologies with modern statistical methods of information processing is substantiated. Examples of the use of regression analysis, clustering, correlation analysis, and geostatistics methods for solving problems of monitoring and forecasting natural processes are given. Tabular models for the analysis and monitoring of environmental data are presented.